Achieving NPVR ≥ 80% as technical success of high-intensity focused ultrasound ablation for uterine fibroids: a cohort study - Shuang Li; Meijie Yang; Jingwen Yu; Wangwa Ma; Yongbin Deng; Liang Hu; Jin-Yun Chen (BMC, 2024)
Abstract Objective To report the long-term re-intervention of patients with uterine fibroids after ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation and to analyse the influencing factors of re-intervention in patients in the NPVR ≥ 80% group. Materials and methods Patients with a single uterine fibroid who underwent USgHIFU at our hospital from January 2012 to December 2019 were enrolled. The patients were divided into four groups according to different nonperfusion volume ratio (NPVR). Kaplan-Meier survival curve was used to analyse long-term re-intervention in different NPVR groups, and Cox regression was used to analyse the influencing factors of re-intervention in the NPVR ≥ 80% group. Main results A total of 1,257 patients were enrolled, of whom 920 were successfully followed up. The median follow-up time was 88 months, and the median NPVR was 85.0%. The cumulative re-intervention rates at 1, 3, 5, 8 and 10 years after USgHIFU were 3.4%, 11.8%, 16.8%, 22.6% and 24.1%, respectively. The 10-year cumulative re-intervention rate was 37.3% in the NPVR < 70% group, 31.0% in the NPVR 70-79% group, 18.2% in the NPVR 80-89% group and 17.8% in the NPVR ≥ 90% group (P < 0.05). However, no difference was found between the group of NPVR 80−89% and the group of NPVR ≥ 90% (P = 0.499). Age of patients and signal intensity on T2-weighted imaging (T2WI) of tumours were found to be independent risk factors for long-term re-intervention in the NPVR ≥ 80% group. A younger age and greater signal intensity on T2W images corresponded to a greater risk of re-intervention. Conclusion USgHIFU, an alternative treatment for uterine fibroids, has reliable long-term efficacy. NPVR ≥ 80% can be used as a sign of technical success, which can reduce re-intervention rates. However, an important step is to communicate with patients in combination with the age of patients and the signal intensity on T2WI of fibroids. Trial registration This retrospective study was approved by the ethics committee at our institution (Registration No. HF2023001; Date: 06/04/2023). The Chinese Clinical Trial Registry provided full approval for the study protocol (Registration No. CHiCTR2300074797; Date: 16/08/2023).